Optimalisasi Pelayanan Penyaluran Bantuan Sosial Kantor Pos KCU Surabaya 60000 - ABD BERI; Sugeng Purwanto (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The Indonesian government continues to make positive efforts in dealing with reducing food insecurity and food inflation that is occurring in Indonesia. This is evidenced by the existence of a social assistance distribution activity program in the form of BAPANG (Foodstuffs) to KPM (Beneficiary Families) throughout Indonesia. One of the POS Indonesia Branch Offices that performs distribution services is the Surabaya 60000 Main Branch Office. By carrying out a mature and structured preparation stage, KCU Surabaya 60000 is able to distribute BAPANG social assistance to the fullest. This is evidenced by the total disbursement of 137,879 BAPANG realizations out of a total allocation of 137,879 in phase 1 distribution and as many as 136,388 realizations of distribution out of a total allocation of 137,879 BAPANG in stage 2. Although it can be said that the distribution of BAPANG carried out by KCU Surabaya 60000 has been maximized, it is still there are a number of things that need to be improved so that the maximum amount of BAPANG distributed to KPM (Beneficiary Families) can be maximized.